Antiamoebic Activity of Adenophyllum aurantium (L.) Strother and Its Effect on the Actin Cytoskeleton of Entamoeba histolytica - Herrera-Martínez, Mayra; Hernández-Ramírez, Verónica I.; Hernández-Carlos, Beatriz; Chávez-Munguía, Bibiana; Calderón-Oropeza, Mónica A.; Talamás-Rohana, Patricia (Frontiers in Pharmacology, 2016)
In Mexico, the Adenophyllum aurantium (L.) Strother plant is consumed as an infusion to treat intestinal diseases such as amoebiasis, which is an endemic health problem in Mexico and other countries. However, the effect of A. aurantium on Entamoeba histolytica, the causative agent of amoebiasis, is unknown. An aerial part methanolic extract (AaMeA), a root methanolic extract (AaMeR) and a root ethyl acetate extract (AaEaR) were tested on E. histolytica trophozoites. AaMeA and AaMeR did not show antiproliferative activity; however, AaEaR exhibited an in vitro GI50 of 230 µg/ml, and it was able to inhibit the differentiation of E. invadens trophozoites into cysts. The intraperitoneal administration of AaEaR (2.5 or 5 mg) to hamsters that were infected with E. histolytica inhibited the development of amoebic liver abscesses in 48.5 or 89.0% of the animals, respectively. Adhesion to fibronectin and erythrophagocytosis were 28.7 and 37.5% inhibited by AaEaR, respectively. An ultrastructure analysis of AaEaR-treated trophozoites shows a decrease in the number of vacuoles but no apparent cell damage. Moreover, this extract affected the actin cytoskeleton structuration, and it prevented the formation of contractile rings by mechanism(s) that were independent of reactive oxygen species and RhoA activation pathways. 13C NMR data showed that the major compounds in the AaEaR extract are thiophenes. Our results suggest that AaEaR may be effective in treatments against amoebiasis, nevertheless, detailed toxicity studies on thiophenes, contained in AaEaR, are required to avoid misuse of this vegetal species.